The basics of hacking and penetration testing : ethical hacking and penetration testing made easy - Engebretson, Pat (Patrick Henry), 1974- (Syngress basics series., 2010)
The Basics of Hacking and Penetration Testing serves as an introduction to the steps required to complete a penetration test or perform an ethical hack. You learn how to properly utilize and interpret the results of modern day hacking tools; which are required to complete a penetration test. Tool coverage will include, Backtrack Linux, Google, Whois, Nmap, Nessus, Metasploit, Netcat, Netbus, and more. A simple and clean explanation of how to utilize these tools will allow you to gain a solid understanding of each of the four phases and prepare them to take on more in-depth texts and topics. This book includes the use of a single example (pen test target) all the way through the book which allows you to clearly see how the tools and phases relate. Each chapter contains hands-on examples teach you how to interpret the results and utilize those results in later phases Written by an author who has practical experience as a Penetration Tester and who has taught "Introduction to Penetration Testing" for 5 years Utilizes Backtrack Linux distribution and the "core" tools required to complete a penetration test